Variations of a brand logo: Google’s doodles - Jessen, Iben Bredahl (Academic Quarter | Akademisk kvarter, 2015)
Provisional changes of the well-known Google logo have been a recurring phenomenon on the front page of the search engine since 1998. Google calls them “doodles”. The doodles are variations of the Google logo that celebrate famous individuals or cultural events, but the doodles also point to the iconic status of the Google logo as a locus of creativity and reinterpretation. The article explores the iconic status of the Google logo as expressed in the doodles. On the basis of a multimodal typographic analysis of a sample of Google’s doodles from 1998 to 2013, the article identifies different types of relations between the well-known Google letters and the new graphic features. The article examines how these relations produce and communicate brand iconicity, and how this iconicity has developed from a typographic perspective.